Perusterveydenhuollon ja erikoissairaanhoidon käytön seuranta ja ennakointi kuntanäkökulmasta - Ovaskainen, Päivi (fi=Turun yliopisto|en=University of Turku|, 2005)
Follow-up of utilisation and prediction of primary health care and hospital care from the municipality point of view. Planning, follow-up, and evaluation of primary health care within municipality entail comprehensive information about factors that influence health. In addition to populationbased research, various statistical data and registries serve as sources of information. The present study examined utilisation of primary health care and hospital care with the existing databases, registries, and categorization of Diagnosis Related Groups (DRGs) from the municipality (purchaser) point of view. Research involving the cases of Paimio, Sauvo, and Turku as examples of municipalities pointed out that, even in the small municipalities, it is possible to assess and predict health services to be offered to the inhabitants by following databases and registries. Health-related databases and registries include a plenty of possible uses that have not adequately been employed at the level of municipality. Descriptive futures research and community analysis formed the framework of the study. Descriptive futures research may be used to establish predictions based on past developmental traditions, and quantitative time trend analyses may be employed to make estimations about future events. Community analysis will assist in making conclusions about population- based health care needs, in assessing the functionality or effectiveness of the health care system, and in appropriately targeting limited resources. The aim of the present study was to describe the health service profile so that the arrangements and planning of health services as well as the contract negotiations of hospital care become easier within municipalities. Another aim was to assess the application of Hilmo (registry for posting hospital care periods), Aitta and Sotka (statistical databases) for the purposes of resource planning in the procurement of hospital care. A third aim was to evaluate how the system of the DRGs adapts in the prediction of retaining health services within short (1-year), intermediate (5-year) and long range (10-15-year) intervals. The findings indicated that the follow-up of primary health care utilisation combined with follow-up of hospital care utilisation allows municipalities to plan and predict health services when databases are applied. Information about the past contacts with the databases has indicated that the health care culture and incidence of disease change rather slowly in the area of investigation. For the purposes of health care research, it is recommended that methods of application used in making predictions about health care utilisation need to be further developed

Terveydenhuollon suunnittelu, seuranta ja arviointi edellyttävät kattavia tietoja terveyteen vaikuttavista tekijöistä kunnissa. Tietolähteenä ovat väestötutkimusten lisäksi erilaiset tilastot ja rekisterit. Tässä tutkimuksessa perusterveydenhuollon ja erikoissairaanhoidon käyttöä tarkasteltiin kuntanäkökulmasta (maksajan näkökulma) olemassa olevien tietokantojen, rekisterien ja DRG-ryhmittelyn avulla. Tutkimustyö Paimion, Sauvon ja Turun casekunnissa osoitti, että väestölle annettavat terveyspalvelut ovat analysoitavissa ja ennakoitavissa myös pienissä kunnissa rekisterien ja tietokantojen tietoja seuraamalla. Terveyttä koskevat tietokannat ja rekisterit sisältävät runsaasti käyttömahdollisuuksia, joita ei ole kunnissa riittävästi hyödynnetty. Tutkimuksen viitekehyksinä olivat deskriptiivinen tulevaisuudentutkimus ja yhteisöanalyysi. Deskriptiivisen tulevaisuudentutkimuksen avulla laaditaan menneisyyden kehityslinjoihin perustuvia ennustuksia ja esitetään tulevaisuudesta arvioita esimerkiksi kvantitatiivisten aikasarja-analyysien avulla. Yhteisöanalyysin avulla voidaan tehdä johtopäätöksiä väestön terveystarpeista ja arvioida olemassa olevan terveydenhuoltojärjestelmän toimivuutta ja vaikuttavuutta sekä suunnata rajallisia voimavaroja oikeisiin kohteisiin. Tutkimuksen tavoitteena oli kuvata terveyspalveluprofiilia, joka helpottaisi kuntien terveyspalvelujen järjestämistä ja suunnittelua sekä erikoissairaanhoidon sopimusneuvotteluja. Toisena tavoitteena oli arvioida Hilmo-hoitoilmoitusrekisterin sekä Aitta- ja Sotkatilastotietokantojen käyttöä kunnan resurssisuunnittelussa erikoissairaanhoidon ostojen tilaamiseen. Lisäksi tutkimuksen tavoitteena oli arvioida, miten DRG (Diagnosis Related Groups) –järjestelmä soveltuu terveyspalveluiden käytön ennakointiin lyhyellä (1 v), keskipitkällä (5 v) ja pitkällä aikavälillä (10–15 v). Tutkimuksen tuloksena voidaan todeta, että perusterveydenhuollon käytön seuranta yhdistettynä erikoissairaanhoidon käytön seurantaan tietokantojen avulla antaa kunnille apuvälineen suunnitella ja ennakoida terveydenhuollon palveluitaan. Käytettyjen tietokantojen tiedot osoittivat, että hoitokulttuuri ja sairastavuus muuttuvat tutkitulla alueella hitaasti. Jatkossa terveydenhuollon tutkimuksessa tulisi paneutua hoidon käytön ennakointimenetelmien sovellutusten kehittämiseen.
Keywords: hospitals, special; healt planning; primary health care; community health services; utilization review; ennakointi; perusterveydenhuolto; seuranta; terveydenhuolto; suunnittelu; terveyspalvelut; erikoissairaanhoito